Contrast-Enhanced Ultrasound for Assessment of Local Hemodynamic Changes Following a Rodent Contusion Spinal Cord Injury. (19th February 2020) - Khaing, Zin Z; Cates, Lindsay N; Hyde, Jeffrey; DeWees, Dane M; Hammond, Ryan; Bruce, Matthew; Hofstetter, Christoph P
ABSTRACT: Introduction: Severe trauma to the spinal cord leads to a near complete loss of blood flow at the injury site along with significant hypoperfusion of adjacent tissues. Characterization and monitoring of local tissue hypoperfusion is currently not possible in clinical practice because available imaging techniques do not allow for assessment of blood flow with sufficient spatial and temporal resolutions. The objective of the current study was to determine whether ultrafast contrast-enhanced ultrasound (CEUS) imaging could be used to visualize and quantify acute hemodynamic changes in a rat traumatic spinal cord injury (SCI) model. Materials and Methods: We used novel ultrasound acquisition and processing methods that allowed for measurements of local tissue perfusion as well as for assessment of structural and functional integrity of spinal vasculature. Results: CEUS imaging showed that traumatic SCI results in (1) an area with significant loss of perfusion, which increased during the first hour after injury, (2) structural alterations of the spinal cord vasculature, and (3) significant slowing of arterial blood flow velocities around the injury epicenter. Conclusion: We conclude that CEUS has the spatial and temporal sensitivity and resolution to visualize local tissue perfusion and vessel architecture, which maybe useful clinically to determine injury extent and severity in patients with SCI.